Integrasi Pendidikan Ruhiyah Dalam Moderasi Beragama Bagi Generasi Z: Kajian Tafsir Q.S. Al-A’raf: 172 - Muhsonah, Isma (Journal of Ulumul Qur'an and Tafsir Studies, 2025)
This article aims to examine the relationship between the values of spiritual education derived from Q.S. Al-A’raf: 172 and the strategy for strengthening religious moderation, particularly in the context of shaping the religious character of Generation Z. Spiritual education, which emphasizes human awareness of the primordial covenant with Allah, serves as a crucial foundation in forming a moderate personality—one that is just, balanced, and avoids extremism in religious practice. Through an educational tafsir approach, this study also explores Q.S. Al-Baqarah: 143, which affirms the role of the Muslim community as ummatan wasathan (a moderate nation), and explains how the integration of these two verses can become a strategic foundation in nurturing the religious character of Generation Z. The study finds that deeply internalized spiritual education from an early age can function as a moral compass that prevents deviations in religious behavior. In the context of Generation Z, who live in a digital era with open access to diverse information, awareness of the spiritual covenant can serve as a central guide to return to divine values amidst the rise of permissive ideologies. This research recommends the integration of spiritual values into educational curricula as well as in religious guidance and da’wah methods tailored to the characteristics of Generation Z.